ANALISIS STILISTIKA DALAM NOVEL CAHAYA GUMAWANG DINA ATI KARYA NINGRUM DJULAÉHA - Dea Radina; Fajar Sukma Nur Alam (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research explores the stylistic features in the novel Cahaya Gumawang dina Ati by Ningrum Djulaéha, focusing on how language is used aesthetically to convey meaning, emotion, and cultural values. The study employs a descriptive qualitative method with a content analysis approach, guided by Nurgiyantoro’s stylistic theory, which includes figurative language and rhetorical elements. Data were collected from the second edition of the novel (2022) and analyzed systematically. The results reveal a total of 373 stylistic expressions, consisting of simile, metaphor, personification, metonymy, synecdoche, repetition, parallelism, anaphora, asyndeton, hyperbole, litotes, paradox, irony, rhetorical questions, climax, and antithesis. These elements reflect the author’s skill in creating literary beauty while expressing deep emotional experiences and cultural identity. The findings indicate that stylistic analysis is not only relevant to literary interpretation but also useful for enriching literary studies, particularly in regional literature. Future research may expand this study with interdisciplinary or comparative approaches.